Hubungan Iman Dan Tanggung Jawab Ekologi Dalam Pembelajaran PAI di MTs Al-Ichsan Nanggulan - Fatmawati; Handayana Rehan Pratama; Adjie Fahrezy Husaini; Inayatun Nupus (Al-Khazin: Jurnal Pendidikan Agama Islam, 2025)
The relationship between faith and ecological responsibility in studying Islamic religious education (PAI) is very close. In Islam, faith is not only related to spiritual and ritual aspects, but also includes responsibility towards the environment. Based on Islamic ecotheology, PAI teachings contain environmental care values originating from the Al-Quran and Hadith. The aim of this research is not only in the cognitive realm, but also concerns increasing awareness, attitudes, behavior, skills and participation that lead to environmentally responsible morals and ethics at MTs Al-Ichsan Nanggulan. The planned learning strategy must implement aspects of learning materials, learning strategies and models, as well as support from educational institutions to achieve these goals. This research uses a qualitative approach with observation and interview methods. And there are many references taken from various journals, books and previous research results related to this problem. It is hoped that the results of this research will contribute conceptually and become an inspiration for the development of praxis.